Pengabdian Pelatihan Kelompok Pemandu Geowisata Di Desa Air Batu Kawasan Geopark Nasional Merangin, Kabupaten Merangin, Provinsi Jambi - Anggi Deliana Siregar; D. M. Magdalena Ritonga; Yulia Morsa Said; Shazkya Annura Rizky; Obrin Trianda; Misnawati (ReTII, 2023)
Administratively, Air Batu Village is located in Renah Pemberap District, Merangin Regency, Jambi Province. Air Batu is one of the villages included in the main area of the Jambi Merangin National Geopark which has the potential to be developed into a national and international level tourism area. Air Batu Village has the potential for the development of general tourism sites as well as geotourism as special interest tourism as a sustainable economic improvement. It has a value that can improve the economic life of the community. The community group that will be partnered in community service this time is the Air Batu River Georafting guide group. Currently the community group only guides rafting for tourists who come, it would be nice if each guide also has knowledge of their tourist objects in guiding tourists later.